'Making blockchain real': regulatory discourses of blockchains as a smart, civic service. Issue 12 (2nd December 2021) - Sotoudehnia, Maral
ABSTRACT: Policymakers across Canada are considering the blockchain as a way to enable smart(er) governance. Despite the technology's infancy, jurisdictions perceive smart tools as one of many ways to govern efficiently. Critical geographers, however, remain circumspect of datafication as a value-making process, and have traced myriad ways data-driven technologies participate in the materialization of smart policy mobilities and governance. This article uses autobiography to highlight discourses positioning blockchain technology as a data-driving and -producing civic service. Empirical findings suggest that Canadian policymakers draw on entrepreneurial discourses of digital leadership, transparent data management and digital empowerment to justify their plans in 'making blockchain real'. These regulatory discourses promote datafication through blockchains as a way to improve government services.